2016
DOI: 10.18632/oncotarget.7801
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of lncRNA mediated transcriptional dysregulation dictates lncRNA roles in glioblastoma

Abstract: Long non-coding RNAs (lncRNAs) modulate gene expression, and lncRNA misregulation is associated with cancer. However, precise functional roles in biological and disease processes have been described for only a few lncRNAs. Identification of genome-wide lncRNA-mediated transcriptional dysregulations may improve cancer treatments. In the present study, we used a computational framework that combined lncRNA and gene expression profiles with transcription factor (TF)-target relationships to comprehensively identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 61 publications
(66 reference statements)
1
34
0
Order By: Relevance
“…Non-coding RNAs (including both miRNAs and lncRNAs) have been recently implicated as important regulators of various tumorigenic processes including GBM [ 23 , 25 , 30 ]. Although most studies have explored the roles of miRNAs [ 40 ], recent reports implicated specific lncRNAs as critical factors in determining GBM growth, infiltration and response to therapies [ 23 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-coding RNAs (including both miRNAs and lncRNAs) have been recently implicated as important regulators of various tumorigenic processes including GBM [ 23 , 25 , 30 ]. Although most studies have explored the roles of miRNAs [ 40 ], recent reports implicated specific lncRNAs as critical factors in determining GBM growth, infiltration and response to therapies [ 23 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of lncRNAs has been recently characterized in GBM [ 22 , 23 ] and lncRNA signatures and profiles in various GBM subtypes [ 24 ] and in association with patient prognosis [ 25 , 26 ] have been identified. Moreover, the roles of specific lncRNAs such as H19 [ 27 ] and MALAT1 [ 28 ] have been described in various functions of glioma cells [ 29 , 30 ], whereas the function of lncRNAs in the functions of GSCs is just beginning to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, some other regulatory issues (such as transcription factors or miRNAs) still need to be addressed for investigate the detail mechanism. In addition, the mechanisms of action of lncRNAs are diverse and include RNA-RNA, RNA-DNA, and RNAprotein interactions [45]. Evidence has shown that MIR22HG is a target of miR-141-3p in endometrial carcinoma [46].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we established a computational method for identification the modulators whose expression is associated with changing the targets splicing outcomes of RBPs in KIRC. Previously, several computational methods have been developed to identify modulators associated with transcription factors (TFs) regulation activity on expression level (Wang et al, 2009;Babur et al, 2010;Li et al, 2016Li et al, , 2017, these studies discussed the transcriptional activities of TFs can be influenced by the expression level of modulators. Our method is unique in its ability to discover how alternative splicing outcomes is changing when modulator expression is different, even though they were regulated by the same RBP.…”
Section: Discussionmentioning
confidence: 99%